Self-Regulated Resource Management in Emergency Remote Higher Education: Status Quo and Predictors - Naujoks, Nick; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert; Händel, Marion (Frontiers in Psychology, 2021)
Because of the COVID-19 pandemic in the spring term 2020, students faced a sudden change from on-campus learning to online learning with synchronous and asynchronous online courses (emergency remote teaching). To study successfully, students not only needed to be prepared in terms of digital readiness (workspace, IT equipment, previous online learning experiences, and sharing information online), they also faced challenges that pertained to the self-regulated management of external resources (environment structuring, time management, and help-seeking). In the current study, we investigated students’ digital readiness for the sudden switch to online learning; differences between students’ intended and actual use of external resource management strategies; and the influence of students’ digital readiness on their actual use of resource management strategies. Students enrolled in a full-scale, German university (N = 662) answered two online questionnaires (before and in the middle of the term). Descriptive statistics indicated that students seemed to be ready to study online. However, a repeated measures analysis of variance showed that students were not able to manage their resources during the term as frequently as intended. Finally, separate regression analyses revealed that availability of workspace and IT equipment predicted the use of environment structuring strategies. Additionally, IT equipment and information sharing behavior predicted students’ help-seeking. Based on the current results, we discuss implications for the promotion of student self-regulated learning in online emergency remote teaching based on both external resources and digital readiness.